1968
DOI: 10.1161/01.res.22.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Circulating Renin and Erythropoietin in Rats

Abstract: Renin and erythropoietin activities were measured in the plasma of 110 rats exposed to various conditions designed to dissociate the two renal "hormones." In acute experiments, intraperitoneal injection of polythiazide increased renin activity but did not change erythropoietin activity; exposure to low oxygen tension increased erythropoietin activity and caused an insignificant decrease in renin activity. In chronic experiments, salt restriction or the combination of salt loading and desoxycorticosterone for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1968
1968
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Thus, while closure of small vessels may be the basic event precipitating release of both renin and erythropoietin during rejection, it appears that the actual stimuli for release of the two substances are different. This concept agrees with the work of Donati and associates (12), who found that rats subjected to a combination of chronic saline loading and acute hypoxia had reduced plasma renin activity and increased plasma erythropoietin activity. They also found that exposure of rats to low oxygen tension increased erythropoietin activity and caused an insignificant decrease in renin activity.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, while closure of small vessels may be the basic event precipitating release of both renin and erythropoietin during rejection, it appears that the actual stimuli for release of the two substances are different. This concept agrees with the work of Donati and associates (12), who found that rats subjected to a combination of chronic saline loading and acute hypoxia had reduced plasma renin activity and increased plasma erythropoietin activity. They also found that exposure of rats to low oxygen tension increased erythropoietin activity and caused an insignificant decrease in renin activity.…”
Section: Discussionsupporting
confidence: 92%